Cryptogenic Multifocal Ulcerous Stenosing Enteritis: An Exceptionally Rare Disease - Amandeep Kaur; Ramesh Chavan; Ranjit Kangle; Bhagyashri Hungund (Journal of Krishna Institute of Medical Sciences University, 2016)
Cryptogenic Multifocal Ulcerous Stenosing Enteritis (CMUSE) is a rare idiopathic disease of the small bowel. Its origin and pathophysiology has not been well described. Clinicopathologic features include unexplained ileal strictures with supercial ulceration. We present a case of a 31-year-old HIV positive lady who was admitted with complaints of recurrent abdominal pain and constipation. Laboratory investigations revealed iron deciency anemia. Ultrasonography of the abdomen showed dilated bowel loops and a subsequent barium follow through showed ve strictures in the ileum. Segmental small bowel resection with end-to-end anastomosis was performed. Grossly ileum showed ve ileal strictures. The diagnosis of CMUSE was made on histopathology after ruling out other causes of strictures. The present case highlights the importance of considering CMUSE in patients with chronic or recurrent episodes of intestinal obstruction with multiple small intestinal ulcers and strictures after other common causes have been ruled out.